How influential is politics for Indonesia? - Naswa, Nabila (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The relationship between law and politics, as discussed in the field of legal studies, examines how law operates within a specific political context. The term "legal politics" consists of two words: politics and law. Etymologically, the relationship between politics and law in the context of legal politics can be explained as follows: In the Dutch language, the term for legal politics is "rechtspolitiek." Rechtspolitiek is a compound word consisting of "recht" (law) and "politiek" (politics). The word "recht" refers to the system of rules that govern behavior in society, known as law. On the other hand, "politiek" or "beleid" means politics (policy). Legal politics is the exercise of power with rights and authority over a law. It serves various purposes: 1) In the socio-political sphere, legal politics aims to ensure justice in society. It strives for the application of fair rules for the community, avoiding any biases or favoritism, both in laws and other regulations, 2) Legal politics is beneficial in maintaining legal certainty to create a sense of security and tranquility in society. All rules, whether new or existing, should be based on reliable and logical sources. Rules should be used appropriately and in accordance with the law dan 3) In concrete social life, legal politics aims to regulate genuine interests. This is applied, for example, when the government enacts laws that align with the collective aspirations of society and support them.